HUBUNGAN FAKTOR LINGKUNGAN KERJA DAN FAKTOR INDIVIDU TERHADAP RISIKO PENINGKATAN TEKANAN DARAH PEKERJA PT ANTAM TBK UBPE PONGKOR BOGOR TAHUN 2023 - Susthania Syifra Yohana (2024)
Hypertension is the main cause of premature death in the worldwide. Data from Riskedas 2018 shows that hypertension predominantly happened in workers, both formal and informal workers, with a prevalence rate of 36,9%. Hypertension, characterized by increased blood pressure, is stems from various factors, such as individual factors and work environment factors. This research aims to determine the relationship between individual factors and work environment factors in the increasing of blood pressure among workers. The research population consisted of shift workers at PT Antam Tbk UBPE Pongkor with a total sample of 125 workers selected through simple random sampling technique. The research instruments such as digital sphygmomanometer, Sound Level Meter, Wet Bulb Globe Temperature, Glover Nilsson Smoking Behavioral Questionnaire, Pittsburgh Sleep Quality Index, The Baecke Habitual Physical Activity Questionnaire, and Perceived Stress Scale. This research employed a cross-sectional study design with Chi-Square test. The research results indicate a correlation between age, smoking behavior, stress, and noise with an increased blood pressure. It can be concluded that there is a relationship between individual factors and work environment factors in increasing blood pressure. The advice given is to adopt a clean and healthy lifestyle and utilization of PPE.